Financial behavior, self-efficacy, and entrepreneurial skills: Uncovering the determinants of culinary business performance - Mawardi, Moh. Cholid; Handayati, Puji; Mukhlis, Imam; Hermawan, Agus; Soetjipto, Budi Eko (The Economics and Finance Letters, 2025)
The culinary industry is a prominent sector with rapid growth, which contributes to the creative economy and small- to medium-sized enterprises. Hence, understanding the determinants of factors affecting culinary businesses will help enhance financial performance and business sustainability among culinary small- to medium-sized enterprises in Indonesia. This present study examines the impact of financial behavior, financial self-efficacy, and entrepreneurial skills on the business performance of culinary small- to medium-sized enterprises. The Partial Least Squares (PLS) Structural Equation Modeling (SEM) approach was used to analyze data obtained from 110 culinary small- to medium-sized enterprises in Indonesia. The data were gathered using a self-administered survey employing questionnaires on a Likert scale. The results of this study show that financial behavior and entrepreneurial skills can promote business performance in the culinary sector. However, the variable of financial self-efficacy failed to stimulate the business performance of culinary small- to medium-sized enterprises. These findings underline the importance of developing good financial behavior and entrepreneurial skills to improve business performance among small- to medium-sized enterprises. Additionally, the findings of this research can provide insights for educational institutions, business incubators, and policymakers in designing more effective training programs to enhance business performance and sustainability. The results of this work complement previous studies and provide insights for stakeholders and policy scholars in supporting business development strategies.